2018
DOI: 10.7717/peerj.6052
|View full text |Cite
|
Sign up to set email alerts
|

Importance of biotic predictors in estimation of potential invasive areas: the example of the tortoise beetleEurypedus nigrosignatus, in Hispaniola

Abstract: Climatic variables have been the main predictors employed in ecological niche modeling and species distribution modeling, although biotic interactions are known to affect species’ spatial distributions via mechanisms such as predation, competition, and mutualism. Biotic interactions can affect species’ responses to abiotic environmental changes differently along environmental gradients, and abiotic environmental changes can likewise influence the nature of biotic interactions. Understanding whether and how to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 54 publications
1
13
1
Order By: Relevance
“…We suggest an integrative approach for SDMs which include biotic and climatic predictors, as indicated by other authors (Palacio and Girini 2018;Simoes and Peterson 2018). Our results also highlight that SDMs applied without a biological purpose do not make sense.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We suggest an integrative approach for SDMs which include biotic and climatic predictors, as indicated by other authors (Palacio and Girini 2018;Simoes and Peterson 2018). Our results also highlight that SDMs applied without a biological purpose do not make sense.…”
Section: Discussionsupporting
confidence: 73%
“…Even so, inventories are not usually done simultaneously by researchers from different groups and we then raised the possibility that results highlight the importance of knowing the biology of the modelled species. Notwithstanding the controversy of considering biotic predictors as determinant in species distribution, this seems to be a pattern corroborated by several studies (Meier et al 2011;Meineri et al 2012;Araújo and Rozenfeld 2013;Giannini et al 2013;Palacio and Girini 2018;Simoes and Peterson 2018). Such a pattern seems to repeat itself especially for endotherms, since the distribution of ectotherms may be directly related to climate conditions instead of biotic interactions, and the addition of biotic predictors may increase model complexity and decrease model performance (Engler et al 2013), unless species have a strong biotic interaction.…”
Section: Discussionmentioning
confidence: 69%
“…2013, Atauchi et al. 2018, Simões and Peterson 2018, Bebber and Gurr 2019). Some studies have underlined the importance of including biotic factors in model calibration, although over interpretation of data is a concern, without denying the possibility that biotic interactions may increase the accuracy of niche model results (Dormann et al.…”
Section: Discussionmentioning
confidence: 99%
“…Moving from single-species models to multispecies models by including biotic interaction perspectives may provide additional important information about direct versus indirect roles of biotic interactions and thus illuminates the processes involved still more (Dormann et al 2018). Previous studies have indicated that ecological niche models improve when biotic interactions among species are incorporated (Ara ujo and Luoto 2007, Giannini et al 2013, Atauchi et al 2018, Simões and Peterson 2018, Bebber and Gurr 2019. Some studies have underlined the importance of including biotic factors in model calibration, although over interpretation of data is a concern, without denying the possibility that biotic interactions may increase the accuracy of niche model results (Dormann et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation